Observations of the effects of magnetic topology on the SOL characteristics of an electromagnetic coherent mode in the first experimental campaign of W7-X. (7th February 2018) - Liu, S.C.; Liang, Y.; Drews, P.; Krämer-Flecken, A.; Han, X.; Nicolai, D.; Satheeswaran, G.; Wang, N.C.; Cai, J.Q.; Charl, A.; Cosfeld, J.; Fuchert, G.; et al.
Abstract: Turbulence is considered to play an important role in the edge cross field heat and particle transport in fusion devices. Scrape-off layer (SOL) turbulence characteristics were measured by the combined probe mounted on the multi-purpose manipulator during the first experimental campaign of W7-X. An electromagnetic coherent mode (EMCM) at 7 kHz has been observed by multiple diagnostics in both the plasma core and the SOL and exhibits a strong dependence of the magnetic topology. As demonstrated by the measurements of the combined probe, the EMCM starts to appear at a radius of R = 6.15 m along the path of probe measurement and this location is shifted inwards in higher iota configurations. It propagates along the direction of electron diamagnetic drift in the far SOL with a poloidal velocity about 0.6 km s −1 while it turns to the opposite direction gradually in the near SOL in the laboratory frame, but keeps a velocity of about 0.6–0.7 km s −1 along the direction of electron diamagnetic drift in the plasma frame. This mode can be induced by raising the ECRH heating power in similar discharge conditions, which is probably linked to the gradient of electron temperature and pressure. The EMCM is enhanced significantly in the edge magnetic island with long connection length where the EMCM can grow up due to the long particle confinement time.